EVALUASI REALISASI ANGGARAN DI BIDANG PROFESI DAN PENGAMANAN POLDA KEPULAUAN BANGKA BELITUNG DI PANGKALPINANG - Miranti; Panjaitan, Fery; Prima Nugroho, Stefanus (Jurnal Akuntansi Bisnis Dan Keuangan, 2019)
This study aims to determine whether the budget realization from 2014 to 2018 is in accordance with the established budget. Benchmarks in this research is to look at the realization of the budget in the Professional and Security Sector of the Bangka Belitung Islands Polda in Pangkalpinang. The results of the analysis as a whole that Bidpropam has realized or absorbed the budget properly, even though some of them exceed the budgeted budget this is not because of irregularities but because there are additional personnel that were not planned in advance. But the average Bidpropam Polda kep. Babel has realized its budget well this is proven based on realization data from 2014 to 2018, in general reaching 90% and above, although not reaching 100%.